2010
DOI: 10.1536/ihj.51.193
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-Controlled Cooled-Tip Radiofrequency Ablation in Left Ventricular Myocardium Avoidance of Steam Pop During Ablation

Abstract: SummarySteam pop and intramural charring have been reported during cooled-tip radiofrequency catheter ablation (RFCA). We studied the feasibility of temperature-controlled cooled-tip RFCA in the canine heart.An internally cooled ablation catheter was inserted into the left ventricle. A custom-made radiofrequency (RF) generator capable of controlling the tip-temperature at the preset level by slow increases in the power was used. Temperature-controlled cooled-tip RF applications were performed at a target tempe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…However, once higher temperature-rise develops inside the myocardium with limited cooling effects, steam-pop-induced myocardial disruption can occur in some cases. [12][13][14] To avoid this complication, TID around 20 ohm has been used in UNIP ablation. 6,7 However, in several studies, 9,15 these indexes were reported to be insufficient to prevent the occurrence of steam-pop.…”
Section: Steam-pop and Its Predictorsmentioning
confidence: 99%
“…However, once higher temperature-rise develops inside the myocardium with limited cooling effects, steam-pop-induced myocardial disruption can occur in some cases. [12][13][14] To avoid this complication, TID around 20 ohm has been used in UNIP ablation. 6,7 However, in several studies, 9,15 these indexes were reported to be insufficient to prevent the occurrence of steam-pop.…”
Section: Steam-pop and Its Predictorsmentioning
confidence: 99%
“…The models considered two internally cooled catheter tip electrodes (7Fr diameter, 4 mm catheter tip), similar to those used in RF cardiac ablation [3,4,18,19]. Although open-irrigated catheters are commonly used for VFW ablation [6], they have been associated with problems of fluid accumulation in the epicardial space (due to saline irrigation) necessitating frequent aspirations before each lesion [20].…”
Section: Computer Modelingmentioning
confidence: 99%
“…We modeled an internally-cooled catheter, and although these catheters are used for clinical RF ablation of cardiac tissue [3,4,18,19], other types of catheters, such as non-irrigated and open-irrigated catheters, are also employed for this type of intervention. The conclusions reached in this study could therefore be different when using other catheter designs.…”
Section: Study Limitationsmentioning
confidence: 99%
“…Furthermore, we have previously reported that steam pop could be prevented by slowly increasing the RF power automatically to the preset temperature to 40°C. 30 Thus, monitoring catheter-tip temperature and changes in impedance might be useful for preventing steam pop. However, the upper limit of the catheter-tip temperature and lower limit of the decrease in impedance should be determined individually for each ablation system.…”
Section: Discussionmentioning
confidence: 99%